Multi-level governance of Arctic marine plastic pollution: effectiveness and enhancement approaches - Zhang, Jiajia; Yan, Xinqi (Frontiers in Marine Science, 2025)
Marine plastic pollution (MPP) poses a significant threat to the sustainable development of the Arctic. In response, a multi-level governance framework has emerged across global, regional, and national dimensions. At the global level, international agreements such as the United Nations Convention on the Law of the Sea (UNCLOS), the International Convention for the Prevention of Pollution from Ships (MARPOL), and the Code of Conduct for Responsible Fisheries (CCRF) provide foundational regulatory frameworks for marine plastic pollution governance. Regionally, the Arctic Council plays a pivotal role by leveraging initiatives such as the Protection of the Arctic Marine Environment (PAME) and the Arctic Monitoring and Assessment Programme (AMAP). These mechanisms serve to integrate Arctic issues into the global agenda while facilitating knowledge sharing and implementing tailored action plans. Nationally, the eight Arctic states interact with both global and regional governance regimes, participating in collaborative efforts to mitigate marine plastic pollution. However, the effectiveness of multi-level governance of Arctic marine plastic pollution is constrained by regime robustness and state capacity. To more effectively tackle marine plastic pollution in the Arctic, it is imperative to integrate Arctic concerns into global governance agendas, actively build a multidimensional governance framework at the regional level, and enhance the Arctic states’ willingness and capacity—with attention to the contributions and demands of Indigenous communities regarding this issue.